Analisis Pengelolaan Kas Pada Kantor Camat Amarasi Selatan - Adriana Lopo (STIKes Ibnu Sina Ajibarang, 2023)
Regional financial management at the South Amarasi District level continues to undergo regulatory adjustments so that it is more effective and efficient, making planning, budgeting, implementation, administration, reporting, accountability and supervision of regional finances easier. This research is aimed at finding out cash management in South Amarasi District using qualitative descriptive methods. The research results show that cash management follows existing regulations but is not yet optimal due to limited human resources, so it is necessary to prepare competent human resources in cash management and optimize regional financial reports through increasing control functions.